Crime, recidivism and mental disorders among prisoners in Mbarara municipality, southwestern Uganda - Forrya, Jimmy Ben; Kirabiraa, Joseph; Ashabaa, Scholastic; Rukundo, Godfrey Zari (International Journal of Law and Psychiatry, 2018)
Introduction: Mental disorders among prisoners have been linked to the type of crime and recidivism. Identification of the mental disorders associated with the different types of crimes and recidivism is essential in the planning and eventual service provision to the prisoners. This study aimed to determine the association between mental disorders, type of crime and recidivism among prisoners in Mbarara municipality in Uganda. Methods: This was a prison facility based cross-sectional study among 414 male and female inmates in Mbarara municipality conducted from June to July 2017. Participants were enrolled from 3 prison facilities through simple random sampling. Sociodemographic-clinical factor questionnaires, and the M.I.N.I. Version 6.0 were completed by each participant. Bivariate and multivariate logistic regression analyses were conducted to determine the associations between the various mental disorders, type of crime and recidivism using the individual adjusted odds ratios at 95% CI. Data were analyzed using STATA 12.0. Results: Of all the 414 participants in this study; 94% were male, 60% were aged 22–35 years, 89% were first-time offenders, and 64% had allegedly committed or been convicted of violent crimes. Social anxiety disorder was significantly associated with non-violent crimes. Major depression was more likely to occur in recidivists whereas panic disorders were more frequent among first-time offenders regardless of their gender. Conclusions: An association was established between the category of crime, recidivism, and type of mental disorder among prisoners participating in the study in Mbarara municipality, southwestern Uganda. Additional findings were that a majority of the prisoners with mental disorders seek health care services from the prison health facility and of these inmates, few are accessing psychiatric treatment.
Keywords: Crime; Recidivism; Mental disorders; Among prisoners; Mbarara municipality; southwestern Uganda